2017
DOI: 10.1111/cxo.12455
|View full text |Cite
|
Sign up to set email alerts
|

Using corneal confocal microscopy to track changes in the corneal layers of dry eye patients after autologous serum treatment

Abstract: The results demonstrate the ability of corneal confocal microscopy to evaluate an improvement in the basal epithelial cell layer of the cornea after autologous serum treatment in patients with dry eye disease. More studies with longer follow-up periods are needed to elucidate the suitability of corneal confocal microscopy to follow the effect of autologous serum treatment on nerve fibres or other corneal layers in dry eye disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Patient symptoms were assessed subjectively using a survey questionnaire symptom score. There was statistically significant improvement in the subjective symptom score in 6 of 10 studies, 7,8,10,13,14,16 and there was improvement that was not statistically significant in 2 studies. 9e11 One study reported no change in symptom scores, 15 and the final study did not report on patient symptoms.…”
Section: Severe Dry Eye Diseasementioning
confidence: 89%
“…Patient symptoms were assessed subjectively using a survey questionnaire symptom score. There was statistically significant improvement in the subjective symptom score in 6 of 10 studies, 7,8,10,13,14,16 and there was improvement that was not statistically significant in 2 studies. 9e11 One study reported no change in symptom scores, 15 and the final study did not report on patient symptoms.…”
Section: Severe Dry Eye Diseasementioning
confidence: 89%
“…The balance of uid in corneal stroma is regulated by multiple tight junctions of endothelial cells and the action of Na + /K + ATPase pump. In this study, we found that corneal thickness increase signi cantly in the control group.Considering that the internal barrier function of the cornea was destroyed to make the uid in matrix unbalance [18].The function of mitochondria was destroyed, ATP production was decreased in corneal endothelial cells and epithelial cells,the permeability of endothelial cells was increased,these pathological changes destroyed the tight junction and Na + /K + ATPase pump function and aggravated matrix edema [19].And these abnormal changes were related to the age of diabetic patients [20].The corneal thickness was signi cantly lower in the treatment group,indicating that the function of corneal internal and external barrier was slightly damaged by dry eye disease and hyperglycemia, and the discomfort was further alleviated and visual function were further improved.…”
Section: Discussionmentioning
confidence: 99%
“…Levy et al [64] also reported an increase in corneal sub-basal nerves and a decrease in dendritic cell density after 6 months of treatment with topical 0.05% cyclosporine in Sjögren's syndrome. IVCM also demonstrated decreased corneal basal epithelial cell density and reduced numbers of nerve beadings after treatment with autologous serum eye drops [65,66].…”
Section: In Vivo Confocal Microscopymentioning
confidence: 93%